Cloning and sequencing of PYBP, a pyrimidine-rich specific single strand DNA-binding protein. - Brunel, F (1991)
In the human transferrin gene promoter, PRI and DRI are positive cis-acting elements interacting respectively with two families of proteins, Tf-LF1 and Tf-LF2. In this paper, we report the purification from rat liver nuclei, of one of these factors, PYBP, as well as the cloning and the sequencing of its cDNA. PYBP is a DNA-binding protein, purified as a 58 kDa doublet which binds only to single strand pyrimidine-rich DNA present for example in PRI and DRI. The protein binds also to a similar polypyrimidine tract present in one of the two strands of a DNA regulatory element of the rat tyrosine aminotransferase gene enhancer. PYBP gene is transcribed ubiquitously as a roughly 2.8 kb RNA which is likely to be subject to an alternative splicing. PYBP is highly homologous to a mouse nuclear protein, as well as to PTB, its human version, which interacts specifically with the pyrimidine tracts of introns. Primary structure information and predicted secondary structure elements of the protein indicate that PYBP contains four sequence repeats. Each of these repeats appears to exhibit the typical RNA recognition motif found in several proteins interacting with RNA or single strand DNA. Finally several hypotheses concerning the biological function of PYBP are presented.